FREQUENCY OF ADVERSE FETOMATERNAL OUTCOMES IN PATIENTS WITH PREECLAMPSIA - Saeed, Kalsoom; Akbar, Saima; Sumayya; Habib, Asia; Amina , Noor ul; Fayyaz, Faiza (Khyber Journal of Medical Sciences, 2024)
Background; Preeclampsia is defined by a systolic blood pressure above 140mmHg and/or diastolic blood pressure above 90 mm Hg associated with proteinuria above or equal to 0.3 g per 24 hours after 20 weeks of gestation. Although globally a lot of work has been done on this topic, there are not enough data available from Pakistan, especially in this part of world. Methodology; this cross-sectional study was conducted in department of obstetrics and gynecology, QHAMC Nowshera from 20th September 2021 to 20th march 2022. A total of 139 pregnant women with preeclampsia were included in the study. All patients were followed till delivery and adverse fetomaternal outcomes were noted as per operational definitions. Results: Age range in this study was from 18 to 40 years with mean age of 27.712±2.77 years, mean gestational age 28.841±3.12 weeks and mean parity was 1.021±1.35. Male patients were 50.5% and females were 49.5%. Placental abruption was observed in 30.9% patients, disseminated intravascular coagulation 35.3%, postpartum hemorrhage 19.4%, acute renal failure 23, intrauterine growth restriction 5.8%, preterm birth 8.6%, intrauterine death 7.2%, low birth weight 10.1% and NICU admission was 51.8%. Conclusion: Pregnancy-related hypertensive disorders are common and adversely impact maternal and fetal outcomes.